Cost accounting - Deakin, Edward B.; Maher, Michael W. (Homewood, Illinois : Irwin Inc., 1987)
Cost accounting is experiencing dramatic changes. Developments in computer systems have reduced manual bookkeeping. Changing production methods in both service and manufacturing industries have made labor-intensive applications of cost accounting obsolete in some cases. There is an increasing emphasis on cost control in hospitals, in industries facing extensive foreign competition, in government, and in many other organizations that traditionally have not focused on cost control. We believe it is important for students to understand fundamental cost accounting concepts, to appreciate how those concepts are applied in prac-tice, and to see how they need to be adapted to accommodate nonmanufacturing applications and changing production technologies. For example, the chapters on cost systems discuss the use of costs for computing inventory values and cost of goods sold on financial statements, but also apply these ideas to product costing for managerial purposes when there is no inventory. The chapter on job costing includes a section on job costing in service organizations, like CPA firms. The discussion of cost allocation shows possible product cost distortions if costs in automated plants are assigned to products using traditional labor-based application methods.
Part One. Cost Accounting System -- Part Two. Differential Cost for Decision making -- Part Three. Cost Data for Performance evaluation -- Part Four. The impact of Uncertainty on Cost Analysis.
Includes bibliographical references and index.
Keywords: COST ACCOUNTING